Ultra-Early Versus Early Aneurysm Surgery After Subarachnoid Hemorrhage: A Retrospective Outcome Analysis - Canotilho Lage, António; Carvalho, Miguel Trigo; Pereira, Ricardo; Gonçalves, Jorge; Matos, Ana; Henriques, Carla; Barbosa, Marcos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Object The timing of definitive management of ruptured intracranial aneurysms has been the subject of considerable debate, although the benefits of early surgery (until 72 hours postictus) are widely accepted. The aim of the present study is to evaluate the potential benefit of ultra-early surgery (until 24 hours) when compared with early surgery, in those patients who were treated by surgical clipping at the Neurosurgery Department of the Coimbra Hospital and University Centre.Methods A 17-year database of consecutive ruptured and surgically treated intracranial aneurysms was analyzed. Outcome was measured by the Glasgow Outcome Scale (GOS). Baseline characteristics were analyzed by the Fisher exact test, the chi-squared and Mann-Whitney tests. Logistic regression was used to assess the impact of good grade according to the World Federation of Neurological Surgeons (WFNS) scale and ultra-early surgery in a good GOS outcome.Results 343 patients who were submitted to surgical clipping in the first 72 hours post-ictus were included, 165 of whom have undergone ultra-early surgery. Demographics and preoperative characteristics of ultra-early and early surgery patients were similar. Good-grade patients according to the WFNS scale submitted to ultra-early surgery demonstrated an improved GOS at discharge and at 6 months. Poor-grade patients according to the WFNS scale submitted to ultra-early surgery demonstrated an improved GOS at discharge.Conclusions Ultra-early surgery for aneurysmal subarachnoid hemorrhage patients improves outcome mainly on good-grade patients. Efforts should be made on the logistics of emergency departments to consider achieving treatment on this timeframe as a standard of care.
Keywords: aneurysm; early surgery; subarachnoid hemorrhage; ultra-early surgery; neurosurgical clipping